PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK SARIAYU MARTHA TILAAR - Yuliani, Vina (Universitas Mercu Buana, 2025)
This study aims to determine the effect of brand image, product quality and trust on consumer purchasing decisions for Sariayu Martha Tilaar cosmetic products. This type of research uses quantitative. The number of samples used in this study were 145 respondents who used Sariayu Marta Tilaar cosmetics in south Jakarta. The population in this study are consumers who use Sariayu Martha Tilaar cosmetic products. Data was collected through a questionnaire. This study uses SEM data analysis techniques and data processing using PLS. The results of this research show that Brand Image, Product Quality, and Trust have a positive and significant influence on purchasing decisions for Sariayu Martha Tilaar cosmetic products in DKI Jakarta.